1996
DOI: 10.1530/jrf.0.1070183
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient partitioning and fetal growth in rapidly growing adolescent ewes

Abstract: A highly controlled model to investigate nutrient partitioning and the control of fetal growth in the rapidly growing adolescent sheep is described. Embryos recovered from superovulated adult ewes inseminated by a single sire were transferred in singleton to the uterus of prepubertal adolescent recipients induced to ovulate at 21 weeks of age (liveweight 44.4 +/- 0.38 kg). After embryo transfer, the adolescent recipients were individually offered a high (n = 28) or low (n = 20) quantity of a complete diet calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 4 publications
12
106
3
2
Order By: Relevance
“…The effects of oversupply of nutrients during mid-pregnancy on foetal development have been less well studied than the effects of undersupply of nutrients. With singleton-bearing adolescent sheep, oversupply of nutrients throughout pregnancy promotes maternal tissue synthesis at the expense of the nutrient requirements of the gravid uterus (Wallace et al, 1996(Wallace et al, , 2001. However, the same group (Wallace et al, 2005), when working with adult sheep, found no differences between the treatment groups in placental or foetal weight.…”
Section: Introductionmentioning
confidence: 92%
“…The effects of oversupply of nutrients during mid-pregnancy on foetal development have been less well studied than the effects of undersupply of nutrients. With singleton-bearing adolescent sheep, oversupply of nutrients throughout pregnancy promotes maternal tissue synthesis at the expense of the nutrient requirements of the gravid uterus (Wallace et al, 1996(Wallace et al, , 2001. However, the same group (Wallace et al, 2005), when working with adult sheep, found no differences between the treatment groups in placental or foetal weight.…”
Section: Introductionmentioning
confidence: 92%
“…Severe maternal nutritional restriction may impact more on birth weights of calves of heifers than of cows, particularly among male calves and those of sires with inherently high birth weight of offspring (Hennessy et al, 2002), presumably due to their greater requirements for nutrients compared with female calves and those of sires with inherently low birth weight of offspring. In adolescent sheep fed to attain excessive fatness prior to and during gestation, placental and foetal growth and birth weight are reduced (Wallace et al, 1996 and, although the extent to which over-nutrition of adolescent heifers influences birth weight is not clear.…”
Section: Paritymentioning
confidence: 99%
“…This results in the premature delivery of low birth weight lambs following spontaneous delivery close to term (Wallace et al 1996(Wallace et al , 2001(Wallace et al , 2004a. Inadequate placental development is central to these negative outcomes and by late gestation placental mass is typically reduced by 30-40% and is associated with a corresponding reduction in both uterine and umbilical blood flows (Wallace et al 2002a).…”
Section: Introductionmentioning
confidence: 99%